FROM AVERSION TO ENGAGEMENT: TRANSFORMING EFL HIGHER EDUCATION STUDENTS’ APPROACH TO ENGLISH IDIOMS THROUGH ROLE-PLAYING - Prayuda, Meikardo Samuel; Gultom, Candra Ronitua; Purba, Natalia; Sharhan, Asmaa Nader (English Review: Journal of English Education, 2024)
The goal of this study is to improve EFL students' exposure to English language acquisition while preventing boredom. In order to get insight into the teaching-learning environment of the classroom and the speaking abilities of EFL students, the researcher used classroom action research. She conducted interviews with the English teacher and students as well as performed observations and administered assessments. With deliberate sampling, this method enables the collection of both qualitative and quantitative data. The pre-test, cycle 1 post-test, and cycle 2 post-test results all showed that EFL students' comprehension of idiomatic speech had significantly increased after using role-playing techniques, as recommended by the study. EFL students performed poorly in the first cycle, as evidenced by their average theoretical score of 62.57 and their 28.57% success rate on the practical test. The EFL mean score on the theoretical test increased to 80.00 in the second cycle with modifications, while the practical test success rate increased to 85.71%. This illustrates how the role-playing technique affects idiomatic speech in EFL. The study also discovered that learners prioritize specific word meanings over metaphorical interpretations, in contrast to native speakers. In the end, the study emphasizes how important it is to take perceptions into account while assessing idiom learning and processing.